Reckless - Silver, Elsie (London, UK Little, Brown Book company, 2023)
"He's scorching-hot trouble wrapped up in a drool-worthy package. And he's looking at her like she might be his next meal. Theo Silva. Rowdy bull rider. Notorious ladies' man. Winter Hamilton knows exactly what it means when he eyes her like that. But she's almost free of her toxic marriage and has sworn off men entirely. So all she sees when she looks back at Theo is temptation served up with a heaping side of heartbreak. The man is hard to trust--but, it turns out, even harder to resist. Make that impossible. Because Theo is persistent. And no matter how hard Winter tries to freeze him out, he melts her icy exterior and pulls apart all her defenses. Over a drink in a small-town bar, she finds herself blurting out her deepest, darkest secrets. Then, she spends the singular hottest night of her life with the man she never thought she'd say yes to. He worships her body. He makes her blush. She comes alive beneath his hands. Then she tells him to forget it ever happened. She wants simple, and with him it all feels complicated. It was supposed to be a one-time thing. A secret. But that little plus sign is going to make this secret impossible to keep"-- Provided by publisher.
"Originally self-published in 2023 by Elsie Silver"--Title page verso.
Includes a bonus scene and excerpt from the author's Hopelss (pages [435]-440).
Keywords: Bull riders -- Fiction; Separated women -- Fiction; Man-woman relationships -- Fiction; Unplanned pregnancy -- Fiction; Betrayal -- Fiction; Secrecy -- Fiction; Romance fiction